Embracing the Cascade part 2: clinical decision making in equine gastric disease. (2nd November 2019) - Redpath, Adam; Bowen, Mark
Abstract : Equine gastric disease, previously referred to as Equine Gastric Ulcer Syndrome (EGUS), is now defined as two distinct disorders. Equine Squamous Gastric Disease (ESGD) is a condition of the equine stomach that is predominantly ulcerative. Equine Glandular Gastric Disease (EGGD) describes the disease of the glandular mucosa, typically a non-ulcerative condition of the pyloric region of the stomach. Acid suppression is the mainstay of therapy for ESGD, and oral omeprazole is the only medication authorised for the management of gastric ulcers (i.e. ESGD), where it is generally effective. Alternative (unauthorised) agents are usually only considered where there is treatment failure, and histamine antagonists, other proton pump inhibitors, or long-acting injectable formulations may be useful in those situations. Management of EGGD requires the use of unauthorised medicines, since no medicines are authorised for its treatment. Misoprostol, long-acting injectable omeprazole and a combination of omeprazole with sucralfate have all been described in its management and can be justified in different clinical scenarios, under the prescribing cascade.